Patented portable spirometer based on fluid mechanics and low energy consumption to monitor rehabilitation of Covid-19 patients. (November 2020) - Alvarez, José C.; Raymundo, Carlos; Zapata, Gianpierre; Ronceros, Julio; Flores, Marco; Ruiz, Francisco
Abstract: The evolution of respiratory capacity in convalescent Covid-19 patients must be monitored over time, which is not feasible due to the lack of personal, portable and low cost spirometers that prevent contamination. Here, we propose the design of a portable and personal spirometer, that uses the parabolic movement of a drop of fluid, driven by exhaled air, to measure respiratory capacity. The distance traveled by the drop is correlated with the air and thus, the exhaled air volume. The mechanical design does not require an external energy source and instead relies on the force of the patient's exhalation. The position of the drop can be measured directly using an interchangeable ruler within the spirometer. The research methodology consists in three stages: idea generation, concept definition (patent), and concept feasibility. In this third stage a simulation with Modellus X.04.05 is realized. We have patented the conceptual design of the spirometer, and additionally present a simulation and feasibility determination of the environmentally friendly and low-cost design. The novelty of this patented spirometer is the use of a simple physical principle to solve a complex problem, without using external energy. Therefore, this artifact can be implemented and widely used in the prevention and control of bronchopulmonary diseases.